Epistemic Egoism and the Protestant Uses of Tradition - Kojonen, Erkki Vesa Rope (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2025)
Although ecumenical dialogue has highlighted many commonalities between Protestants, Catholics, and Orthodox, many issues still remain contentious. One often recurring suspicion is that the Protestant idea of sola scriptura inevitably leads to an individualistic religiosity, neglecting the importance of the divinely guided Christian tradition and Christian church teaching for understanding the Bible. In this article, I relate this critique to the idea of “epistemic egoism”, as defined by Linda Zagzebski, and develop an alternative Protestant social epistemology based on tradition as the “democracy of the dead”, error-corrected by sola scriptura. I test this Protestant theological epistemology against two recent criticisms: (1) the “Conciliar Argument Against Protestantism” (CAAP), arguing that Protestantism fails to provide consistent criteria for valuing conciliar authority as a guide to biblical interpretation, and (2) the “Scriptural Argument Against Dogmatic Protestantism”, arguing that sola scriptura, when understood in light of theological disagreement, ultimately becomes self-refuting in the absence of properly guiding theological authority. I argue, however, that sola scriptura is compatible with assigning an important epistemic role to both tradition and community, and that Protestant principles of theological reasoning can be defended further using recent theories in social epistemology.